THE INFLUENCE OF MANAGERIAL OWNERSHIP, BUSINESS RISK, AND FREE CASH FLOW ON DIVIDEND POLICY WITH LIQUIDITY AS A MODERATION VARIABLE - Diana, Wahyu Tiska (Prosiding University Research Colloquium, 2024)
This study aims to find empirical evidence and analyze the effect of free cash flow, managerial ownership, business risk on dividend policy with liquidity as a moderating variable (empirical study on banks listed on IDX for the period 2014-20 20). The sampling method used was the purposive sampling method and 15 company samples were obtained so that 105 samples were obtained which were the object of research. The analysis technique used in this study is multiple linear regression analysis using SPSS where the data is tested using the coefficient of determination (R²) test and t test and F test, as well as MRA (Moderated Regression Analyze) testing. In addition, the data were analyzed with descriptive statistics and classical assumption tests consisting of normality tests, multicollinearity tests, heteroscedasticity tests, and autocorrelation tests. The test results show that free cash flow, Business Risk, Managerial Ownership does not affect the dividend policy partially, Managerial Ownership, Freecashflow, Business Risk simultaneously does not influence on dividend policy. The results of MRA (Moderated Regression Analysis) testing show that liquidity is unable to moderate the relationship between Managerial Ownership, Business Risk and freecashflow to dividend policy.